Study on the impact of the implementation of University of the Philippines portals' entry and exit policies - Gutierrez, Sydney A.; Pediglorio, Christine Joy T.
The research aims to know the impact of the implementation of the UP Car Sticker System. Volume count surveys were conducted and analysis of unsignalized intersections were performed to obtain the reserve capacity and Level of Service of the intersections near the portals. Volume over capacity ratio of the road sections near portals were obtained to get the Level of Service of road sections near the portals. Result showed that the Magsaysay Guerrero intersection has the poorest level of service of F during peak hours. Licensed plate survey was conducted to update the percentage of the through traffic entering and exiting the portals. The percentage of through traffic decreased from 24% last 2013 to 16% this year. The data collected from the volume count and license plate survey were also used to know the effect of through traffic to the congestion of the intersections near the portals. Origin destination survey was also conducted in order to create a profile of through traffic vehicles, specifically their origin, destination, and routes inside the university. Results showed that the highest frequency of through traffic vehicles came from Philcoa-Technohub Area to Katipunan Area.